Nghiên cứu vai trò của nanoclay như một chất trợ tương hợp trong blend CSTN/EPDM - Chương, Bùi; Đa, Lê Như; Hưng, Đặng Việt; Long, Uông Đình; Đạt, Nguyễn Vĩnh; Nam, Hoàng (Vietnam Journal of Chemistry, 2015)
Nanoclay I28E was introduced in NR/EPDM blends by melt mixing and through masterbatchs. Its compatibilization effect was evaluated at high deformation (ultimate tensile testing, saturated swell) and low deformation properties (stretching – unloading cycles) of filled blends in comparison with that of unfilled one. Results showed that there is almost no effect of nanoclay at high deformation degree of rubber blends. In contrary, at low deformation, nanoclay has strong effect on blend properties: the tensile stress of filled blends is higher about 30-60 % than that of unfilled blend. It is assumed that nanoclay being dispersed in rubber matrix at “rough” level – aggregate of 50-100 nm size, has compatibilization effect mainly at low deformation degree of rubber blends.